FROM SISAL REGION TO SISAL TERRITORY: UNVEILING NUANCES OF DELIMITATION PROCESS OF SPATIAL DIFFERENTIATION IN SEMI-ARID REGION OF BAHIA - Moreira Carneiro Santos, Edinusia (2015)
The category “Region” has been traditionally referred to by government policies for planning and control purposes. However, since the beginning of 21st century, with the ascension of Workers Party (PT), the category “territory” has become fundamental for implementing policies or territorial organization. Such adoption, in the political-institutional environment, produced results on Civil society of Sisal region, because the territory has become key word in the speech of social subjects (associations and agricultural cooperatives rural workers Union and non-governmental organizations). Taking this perception into consideration, the objective of the article is to offer reflection that contributes to in-depth debate about surface, political and organizational contents of the processes of use of the idea of region and/or territory to define techniques of application of public policies. Therefore, the text is structured in 3 parts which aim at explaining how, in specific environment, a region become a territory: the differentiation of semi-arid space, official recognition of Sisal Region in Bahia, and emergence of Sisal Territory.